Timing of Paleoproterozoic ultrahigh-temperature metamorphism in the North China Craton: Evidence from SHRIMP U-Pb zircon geochronology - Santosh, M.; Wilde, S. A.; Li, J. H. (Precambrian Research, 2007)
We report SHRIMP U-Pb zircon ages from two samples of Mg-Al granulite and one of normal khondalite from the Khondalite belt of Inner Mongolia, North China Craton. These data constrain the timing of extreme crustal metamorphism at ultrahigh-temperature (UHT) conditions in the region. The UHT indicator assemblages in these rocks include equilibrium sapphirine + quartz, high alumina orthopyroxene + sillimanite + quartz and high temperature perthites. The surrounding khondalites also carry spinel + quartz equilibrium assemblage. Based on the stability of sapphirine + quartz and orthopyroxene + sillimanite + quartz in the matrix assemblages, T > 1000 degrees C and P > 10 kbar for peak metamorphism was estimated in a previous study, with initial isobaric cooling and subsequent isothermal decompression along a broad anticlockwise trajectory. Metamorphic zircons from the UHT rocks are characterized by ovoid shapes with numerous high-order crystal faces and low luminescence in cathodolurninescence (CL) images. As metamorphic temperatures increase, based on the presence of UHT indicator minerals, relict oscillatory zones are progressively destroyed and the grains become uniformly dark in CL. The oldest detrital cores reveal (207)Pb/(206)Pb ages up to 2090 +/- 22 Ma, but most have hL ages of similar to 1970 Ma. Importantly, the highest grade sample with sapphirine-bearing UHT assemblage, contains only a single zircon population with a weighted mean (207)Pb/(206)Pb age of 1919 +/- 10 Ma. This is the same age, within error, as the youngest populations in the other two samples and is interpreted to record the time of UHT metamorphism in the North China Craton. The zircons in the highest-grade sample have unusually high Th/U ratios (average 1.44) for metamorphic zircon, which may prove to be a feature of UHT rocks. The Khondalite belt defines a collisional orogen between the Yinshan block to the north and the Ordos block to the south, that together form the Western Block of the North China Craton. The similar to 1.92 Ga UHT metamorphic event in the North China Craton preceded the collision that amalgamated the North China Craton along the Trans-North China Orogen at similar to 1.85 Ga, but both coincided with the assembly of the Palcoproterozoic supercontinent Columbia. (c) 2007 Elsevier B.V. All rights reserved. Geosciences, Multidisciplinary SCI(E) 207 ARTICLE 3-4 178-196 159